Cystic Fibrosis Foundation otolaryngology care multidisciplinary consensus recommendations. Issue 9 (22nd February 2022) - Kimple, Adam J.; Senior, Brent A.; Naureckas, Edward T.; Gudis, David A.; Meyer, Ted; Hempstead, Sarah E.; Resnick, Helaine E.; Albon, Dana; Barfield, Wayne; Benoit, Margo McKenna; Beswick, Daniel M.; Callard, Eliza; et al.
Abstract: Background: Cystic fibrosis (CF) is a multisystem disease that often requires otolaryngology care. Individuals with CF commonly have chronic rhinosinusitis but also present with hearing loss and dysphonia. Given these manifestations of CF, otolaryngologists are frequently involved in the care of patients with CF; however, there is limited consensus on optimal management of sinonasal, otologic, and laryngologic symptoms. Methods: The Cystic Fibrosis Foundation convened a multidisciplinary team of otolaryngologists, pulmonologists, audiologists, pharmacists, a social worker, a nurse coordinator, a respiratory therapist, two adults with CF, and a caregiver of a child with CF to develop consensus recommendations. Workgroups developed draft recommendation statements based on a systematic literature review, and a ≥80% consensus was required for acceptance of each recommendation statement. Results: The committee voted on 25 statements. Eleven statements were adopted recommending a treatment or intervention, while five statements were formulated recommending against a specific treatment or intervention. The committee recommended eight statements as an option for select patients in certain circumstances, and one statement did not reach consensus. Conclusion: These multidisciplinary consensus recommendations will help providers navigate decisions related to otolaryngology consultation, medical and surgical management of CF‐CRS, hearing, and voice in individuals with CF. A collaborative and multidisciplinary approach is advocated to best care for our patients with CF. Future clinical research is needed utilizing standardized, validated outcomes with comprehensive reporting of patient outcome, effects of modulator therapies, and genetic characteristics to help continue to advance care, decrease morbidity, and improve the quality of life for individuals with CF.